NKB cells: A double-edged sword against inflammatory diseases - Tandel, Nikunj; Negi, Sushmita; Tyagi, Rajeev K. (Frontiers in Immunology, 2022)
Interferon-γ (IFN-γ)-producing natural killer (NK) cells and innate lymphoid cells (ILCs) activate the adaptive system’s B and T cells in response to pathogenic invasion; however, how these cells are activated during infections is not yet fully understood. In recent years, a new lymphocyte population referred to as “natural killer-like B (NKB) cells”, expressing the characteristic markers of innate NK cells and adaptive B cells, has been identified in both the spleen and mesenteric lymph nodes during infectious and inflammatory pathologies. NKB cells produce IL-18 and IL-12 cytokines during the early phases of microbial infection, differentiating them from conventional NK and B cells. Emerging evidence indicates that NKB cells play key roles in clearing microbial infections. In addition, NKB cells contribute to inflammatory responses during infectious and inflammatory diseases. Hence, the role of NKB cells in disease pathogenesis merits further study. An in-depth understanding of the phenotypic, effector, and functional properties of NKB cells may pave the way for the development of improved vaccines and therapeutics for infectious and inflammatory diseases.